Amos and the Beyond Aid Agenda: The 0.7% Target, COVID-19, and Reimagining International Development - Day, Benjamin S. (International journal of public theology, 2020)
Abstract This article draws on the Old Testament book of Amos as a lens for thinking about the aid-giving behaviour of ‘traditional donor’ states at a time of international uncertainty. In the emerging ‘beyond aid’ environment, achieving international development outcomes will require much more than the provision of aid. States and individuals that are serious about contributing to international development will need to ‘go deeper’, actively assessing the development impacts that a wide array of their own behaviours may have on individuals beyond their borders. By bringing key themes from Amos into conversation with characteristics of the international development regime, this article demonstrates why moving away from an aid-centric approach to international development—symbolised by the 0.7% spending target—is proving difficult. At the same time, it reveals how the COVID -19 pandemic has the potential to function as a critical juncture for reimagining international development in line with the message of Amos.